Les espaces sémantiques entre blendings et multivers morphémiquesHommage à Gilles Fauconnier - François Nemo (Corela)
After describing the scientific context of my encounters with Gilles Fauconnier and his work, the paper discusses contrastively Fauconnier’s notion of blending and mental spaces,and the observation that morphemes may be used radially in distinct domains of experience. This issue is first addressed in Grea’s terms (1992), namely by making a distinction between extented/chained metaphors imposing blending and (morphemic) catachresis with no blending. It is then shown that as for the lexicon itself (and not discourse), Lakoff’s view of blendings (e.g. “conversation is war”) does not fit into this distinction and could well be a purely theoretical artefact. After showing that non-chained metaphors may be accounted for as morphemic reboots, it is finally shown that due to morpheme’s polymorphy it is possible to associate in discourse otherwise “radial” uses of a morpheme and hence domains, thus creating an hybrid and transversal mobilisation of morphemes, and this both in metaphorical and non metaphorical utterances.